Epithelial‐mesenchymal transition spectrum quantification and its efficacy in deciphering survival and drug responses of cancer patients - Tan, Tuan Zea; Miow, Qing Hao; Miki, Yoshio; Noda, Tetsuo; Mori, Seiichi; Huang, Ruby Yun‐Ju; Thiery, Jean Paul (EMBO molecular medicine, 2014)
Epithelial‐mesenchymal transition (EMT) is a reversible and dynamic process hypothesized to be co‐opted by carcinoma during invasion and metastasis. Yet, there is still no quantitative measure to assess the interplay between EMT and cancer progression. Here, we derived a method for universal EMT scoring from cancer‐specific transcriptomic EMT signatures of ovarian, breast, bladder, lung, colorectal and gastric cancers. We show that EMT scoring exhibits good correlation with previously published, cancer‐specific EMT signatures. This universal and quantitative EMT scoring was used to establish an EMT spectrum across various cancers, with good correlation noted between cell lines and tumours. We show correlations between EMT and poorer disease‐free survival in ovarian and colorectal, but not breast, carcinomas, despite previous notions. Importantly, we found distinct responses between epithelial‐ and mesenchymal‐like ovarian cancers to therapeutic regimes administered with or without paclitaxel in vivo and demonstrated that mesenchymal‐like tumours do not always show resistance to chemotherapy. EMT scoring is thus a promising, versatile tool for the objective and systematic investigation of EMT roles and dynamics in cancer progression, treatment response and survival. Synopsis A novel EMT scoring method reveals that EMT status does not unanimously correlate with poorer overall and disease‐free survival. Different EMTed tumours show distinct responses to certain chemotherapeutics, with the potential to stratify patients by EMT status. A novel scoring method was developed based on transcriptomics to universally estimate and compare the Epithelial‐Mesenchymal Transition (EMT) phenotype across cancer types. A spectrum of EMT was established across more than 15 cancers using this EMT scoring method. Correlations of EMT status with poorer overall‐ and disease‐free survival were not unanimously observed in all cancers. Differential and preferential responses of EMTed tumours to certain chemotherapeutics were observed, suggesting the potential to stratify patients by EMT status. Graphical Abstract A novel EMT scoring method reveals that EMT status does not unanimously correlate with poorer overall and disease‐free survival. Different EMTed tumours show distinct responses to certain chemotherapeutics, with the potential to stratify patients by EMT status.